Portal vein thrombosis and non-compliance in a high risk patient – a case study - Marczak, Aleksandra; Hordejuk, Michalina; Gołacki, Jakub; Sapuła, Klaudia; Iwaszko-Sochal, Klaudyna (Journal of Education, Health and Sport, 2022)
Portal vein thrombosis is a pathological process that refers to the obstruction of blood flow secondary to thrombus formation. It may be caused by a variety of conditions including cancer, cirrhosis, myeloproliferative neoplasms (eg. polycythemia vera) or surgery in the area of the portal vein (eg. splenectomy). Recent studies suggest that patients with a positive history of SARS-CoV-2 infection have a higher risk of thromboembolic incidents. According to current procedures patients with increased thromboembolic risk should receive anticoagulants. Non-compliance to medical recommendations may develop a disease, directly threatening the patient's health and life. We present a case report of a 69 year old woman with a history of polycythemia vera, recent splenectomy, and SARS-CoV-2 infection who developed massive portal vein thrombosis two days after discontinuation of enoxaparin.